SCIENTIFIC-THEORETICAL ANALYSIS OF THE UPDATES ON "CIVIL LAW" IN THE DRAFT NEW VERSION OF THE CIVIL CODE OF THE REPUBLIC OF UZBEKISTAN - Imomov, Nurillo Fayzullaevich (Educational Research in Universal Sciences, 2022)
This article gives a scientific-theoretical description of Chapter 1 of the Draft of new edition of the Civil Code of the Republic of Uzbekistan (hereinafter - CC) "Civil legislation". The proposed amendment to the Civil Code with the draft was scientifically grounded in the author’s interpretation. In particular, the necessity and importance of inclusion in the Civil Code of two important principles as the basic foundation of civil law: "freedom of expression of participants of civil proceedings" and "property independence of participants of civil proceedings" is based on the doctrine and practice of civil law. At the same time, the article analyses the scientific and methodological aspects of including corporate relations and other types of business relations in the subject matter of civil law. In addition, it was proposed that an important rule regulating relations with state participation should be established in the system of relations regulated by law. The author has also tried to substantiate the correlation between the general and special part of civil law, the need to determine the retroactive effect of it, the necessity to draft the rules of application of space and the need to strengthen the rules of interpretation of law. In addition, the article analyses the legislation of several foreign countries, the views of domestic and foreign scholars, the sources of the relations regulated by the participants, as well as the essence of the proposed changes and additions in the relationship between civil law and international treaties which are signed by the Republic of Uzbekistan.